Emission forecasting from open burning of crop straw and policy analysis: The case for China - Xinyi Liu; Suzi Tu; Jie Liu; Zhichun Liu (Energy Reports, 2023)
The open burning of crop straw releases greenhouse and harmful gases, and pollutants, which hinder the reduction of carbon emissions and attainment of environmental protection commitments in China. In this study, based on the fractional discrete grey model (FDGM (1,1)) and the new information priority discrete grey model (NIPDGM (1,1)), an alternative weighted hybrid discrete grey model (WHDGM (1,1)) coupled with a particle swarm optimization algorithm was developed to forecast the total crop straw production, quantity of crop straw open burning, and burning emissions in China. The results have shown that the proposed WHDGM (1,1) had the highest simulation accuracy compared to NIPDGM (1,1) and FDGM (1,1). Based on the WHDGM (1,1), predictions for annual crop straw production, crop straw open burning, and induced CO, CO2, NOx, and PM2.5emissions are conducted, respectively. By 2025, crop straw production and crop straw open burning will increase by 10.5% and 7.2%, respectively. Relevant CO, CO2, NOx, and PM2.5will be augmented by 7.4%, 7.7%, 5.6%, and 9.6%, respectively. Countermeasures for controlling crop straw open burning and relevant policy suggestions have been discussed. This study offers practical insights and guidance for the strategic control of crop straw open burning, therefore, ensuring the achievement of carbon neutrality and supporting environmental commitment.